E-200 Predictors of good clinical outcome after thrombectomy for distal medium vessel occlusions. (23rd July 2022) - Guenego, A; Lubicz, B
Abstract : Objective: Good clinical outcome predictors have been emphasized in mechanical thrombectomy (MT) for acute ischemic stroke (AIS) with large vessel occlusion (LVO). MT for distal, medium vessel occlusions (DMVO) is still debated. We sought to assess the factors associated with clinical outcome after MT for DMVO. Methods: We retrospectively analyzed the data of consecutive patients who underwent MT for a primary DMVO in one large academic center and aimed to identify the baseline clinical, imaging and MT factors associated with good clinical outcome (defined as modified Rankin scale [mRS] of 0–2) at 3 months. Results: Between January 2018 and January 2021, 61 patients underwent a MT for an AIS with a primary DMVO. Overall, good clinical outcome was achieved in 56% (34/61) of our patients. In multivariate analysis, we identified higher age (ODDS ratio 0.89 [0.83–0.96], p=0.003), puncture to recanalization time (ODDS ratio 0.97 [0.93–0.99], p=0.033), and baseline core volume (ODDS ratio 0.84 [0.75–0.94], p=0.003) as negative predictors of good clinical outcome, while final complete (or near-) recanalization (mTICI 2c-3) was a predictor of good outcome (ODDS ratio 14.19 [1.99–101.4], p=0.008). Conclusion: An older age, a longer puncture to recanalization time and a higher baseline core volume were strongly associated with poor clinical outcomes, while successful recanalization (mTICI 2c-3) was associated with better outcomes after MT for DMVO. Disclosurse: A. Guenego: None. B. Lubicz: None.